Between Creed and Qur’ān - Khaleel Mohammed (International Institute of Islamic Thought, 2012)
Islam’s main document, the Qur’ān, is perceived as the foundation for the religion’s creedal ideas. Throughout the ages, however, Qur’ānic exegesis (tafsīr), like its counterpart endeavors in other established religions, has become subject to circularity. This means basically that while faith-based scholars may declare that their exegeses are based upon reading scripture qua scripture, their interpretations are often conditioned by creedal constructs imposed upon the text. One such issue in Islam revolves around ‘iṣmah, the concept of prophetic inerrancy. A prophet, in the Islamic worldview, is not simply someone who delivers God’s message, but one who is also tasked with being an exemplar. Since the holder of such an office must have impeccable conduct, as well as proficiency in teaching and explaining what God wants for the faith community, it might be assumed that a doctrine of prophetic inerrancy was a logical inevitability. There is a general agreement between Sunnis and Shīʻahs—primarily by rational analysis—on the issue of the Prophet (ṢAAS) being inerrant from major and minor sins. The concept is not clearly spelled out in the Qur’ān, and based on their differences in creedal perception, the two groups, while agreeing on a core idea, differ on certain details ...